Alkaloidal metabolites from Aspergillus felis and their activities against Paracoccidioides brasiliensis. (September 2016) - Mendes, Graziele; de Menezes Oliveira, Djalma; Kohlhoff, Markus; Rosa, Carlos Augusto; de Almeida Alves, Tânia Maria; Zani, Carlos Leomar; Rosa, Luiz Henrique; Johann, Susana; Barros Cota, Betania
Graphical abstract: Highlights: ⿢ New alkaloidal metabolites, cytochalasin Z15E (1 ) and 5- N -acetyl-8- β -isopropyl-ardeemin (4 ), from Aspergillus felis . ⿢ Their structures were established by the analysis of spectroscopic data. ⿢ Seven isolated compounds from A. felis were evaluated against Paracoccidioides brasiliensis . ⿢ Cytochalasin E (3 ) showed antifungal activity against P. brasiliensis with MIC value of 3.6 μM. Abstract: In this study, the fungus Aspergillus felis (strain UFMGCB 8030) was isolated from rocks in the Atacama Desert, Chile. Its CH2 Cl2 extract exhibited antifungal activity (MIC of 1.9 μg/mL) against Paracoccidioides brasiliensis (Pb18), which is the etiological agent for paracoccidioidomycosis. The crude extract was purified, and a new cytochalasin derivative, cytochalasin Z15E (1 ), and one ardeemin derivative, 5- N -acetyl-8- β -isopropyl-ardeemin (4 ), in addition to five known secondary metabolites, rosellichalasin (2 ), cytochalasin E (3 ), gancidin (5 ), pseurotin A1 (6 ), and 2, 4-dihydroxyacetophenone (7 ), were isolated. The structures of these compounds were confirmed by 1D and 2D NMR spectroscopy and HR-ESI⿿MS. Cytochalasin E was the most active compound with MIC an value of 3.6 μM, while the other isolated compounds exhibited weak antifungal activities (MIC values >100.0 μM).